Mechanisms of carrot texture alteration induced by pure effect of high pressure processing. (June 2019) - Sun, Yaxin; Kang, Xulei; Chen, Fang; Liao, Xiaojun; Hu, Xiaosong
Abstract: The pure effect of high pressure processing (HPP) (400–1200 MPa/2 min) on carrot ( Daucus carota L.) texture was investigated with minor influence of adiabatic heating. For carrot hardness and chewiness, 400 MPa result in respective loss of 71.0%, 73.8%, but no further loss was observed as pressure increased. Cohesiveness and resilience were observed to recover as pressure above 1000 MPa. Mechanisms exploration from cellular microstructure showed that carrot cells evolved from orderliness at atmospheric pressure to corrugation, elongation, collapse but partially compaction at 400, 800 and 1200 MPa, respectively, accompanied with movement of cytoplasmic content to intercellular spaces. Principal component analysis (PCA) highlighted the characteristic biochemical responses of HPP-treated carrots with pronounced ion leakage (>70%), hydrogen peroxide accumulation (>128.0%, 800–1200 MPa) and enhanced pectinmethylesterase (PME) activity (>135.2%, 400–1000 MPa). Moreover, molecular weight analysis of pectin polysaccharides showed that HPP triggered pectin depolymerisation, solubilisation of water insoluble pectin and fraction interconversion. Overall, carrot texture is interactively influenced by pressure-induced modifications on cell morphology, membrane integrity and pectin properties. Industrial relevance: Application of HPP in industrial scale is rising. As an essential factor highly linked with freshness, texture alteration during processing is an industrial-concerned issue. This work provides information on textural alteration under a wide pressure range (400–1200 MPa). The reported pressure thresholds triggering different cellular responses of carrot tissue therefore added new theoretical basis for the industrial optimisation of high pressure conditions. The temperature control strategy used could be potentially applied in food industry with the substituted food-friendly pressure transmitting medium, as well as other areas requiring strict temperature control, for instance high pressure extraction. Highlights: HPP resulted in dramatic carrot texture softening. Cell morphology showed different patterns depending on pressure levels. Mechanical and oxidative damages were induced when pressure was over 400, 800 MPa, respectively. HPP triggered depolymerisation and conversion of pectin substances.